Complete liquification time test coupled with solvent fractionation technique to detect adulteration of foreign fats in ghee. (17th October 2016) - Upadhyay, Neelam; Kumar, Anil; Goyal, Ankit; Lal, Darshan
Abstract : Complete liquification time (CLT) test (min:s) exploits the physical property of milk fat as the time required by solid fat to melt completely at a defined temperature. It has been used to detect adulteration of groundnut oil and goat body fat when added singly and in combination with ghee. The Complete liquification time test for samples containing a combination of adulterants was carried out before and after solvent fractionation. The results revealed that adulterants added individually could be detected at higher levels (15%, w/w, groundnut oil in cow ghee; and 10%, w/w, goat body fat in buffalo ghee), while fractionation reduced the detection limit to lowest level (10%, w/w) used in this study.